2009
DOI: 10.1038/ki.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension is an independent predictor of mortality in hemodialysis patients

Abstract: Pulmonary hypertension in patients with end-stage renal disease on hemodialysis is a newly described entity. To determine its impact, we measured selected clinical variables in the survival of 127 hemodialysis patients. Overall, pulmonary hypertension was found in 37 of these patients; it was already prevalent in 17 of them before initiation of dialysis and was associated with severe cardiac dysfunction. In the other 20 it developed after dialysis began, without obvious cause. These two subgroups of patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
2
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(155 citation statements)
references
References 18 publications
7
135
2
7
Order By: Relevance
“…Studies on non-dialysis-dependent stage 5 CKD patients reported that the prevalence of PHT ranges from 9-39% and that the prevalence of PHT is higher in patients undergoing dialysis than in nondialysis patients (9)(10)(11)(12). In the present study the prevalence of PHT in patients with stage 5 CKD not undergoing HD was 58.3%, which is higher than reported earlier (9,11,13,14). In addition, there weren't any significant differences in sPAP or the prevalence of PHT between the patients undergoing and not undergoing HD.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Studies on non-dialysis-dependent stage 5 CKD patients reported that the prevalence of PHT ranges from 9-39% and that the prevalence of PHT is higher in patients undergoing dialysis than in nondialysis patients (9)(10)(11)(12). In the present study the prevalence of PHT in patients with stage 5 CKD not undergoing HD was 58.3%, which is higher than reported earlier (9,11,13,14). In addition, there weren't any significant differences in sPAP or the prevalence of PHT between the patients undergoing and not undergoing HD.…”
Section: Discussioncontrasting
confidence: 56%
“…Accordingly, we think in addition to CKD patients undergoing HD early-stage CKD patients should also be considered high risk patients. In most studies on patients with CKD, sPAP has been estimated as Doppler-derived sPAP and various sPAP cut offs have been used, ranging from 25 to ≥45 mmHg (9,11,(13)(14)(15). In the present study sPAP ≥35 mmHg based on Doppler echocardiography was considered diagnostic for PHT and the high prevalence of PHT in this study may be explained due to the lack of uniformity in diagnostic criteria and sPAP cutoffs in the literature.…”
Section: Discussionmentioning
confidence: 73%
“…Treatments such as phosphodiesterase type 5 inhibitors or endothelin receptor antagonists have not been studied specifically in patients with ESRD and PH. Surgical reduction of AVF should be considered in patients with very high cardiac output in whom improvements in cardiac output and PH by temporary AVF closure has been shown 121, 122, 126, 127. An AVF flow rate ≥2 L/min and cardiac output of ≥8 L/min place patients at high risk of high‐output cardiac failure 128, 129.…”
Section: Ph In Patients With Esrdmentioning
confidence: 99%
“…The definitive treatment for PH in this population is renal transplantation if the etiology is secondary to high cardiac output from AVF. These patients should be considered for renal transplantation as soon as possible 123, 124, 126…”
Section: Ph In Patients With Esrdmentioning
confidence: 99%
“…Распространен ность ЛГ у пациентов с терминальной хронической почечной недостаточностью (ТХПН), находящихся на программном гемодиализе (ПГД), достаточно ве лика и, по данным разных источников, составляет от 38 до 47% [1,2]. В настоящее время ЛГ счита ется одним из независимых предикторов леталь ного исхода в диализной популяции [3,4]. Распро страненность ЛГ после успешной трансплантации почки (ТП) существенно ниже: порядка 5-14% [5].…”
Section: Introductionunclassified